Modalitas Bahasa Retorika Pidato Anas Urbaningrum Berhenti sebagai Ketua Umum Partai Demokrat (Analisis Semiotika M.A.K. Halliday) - Jaka Sindu (Universitas Mercu Buana, 2019)
The purpose of this study is to describe the meaning construction of social semiotics, political relations, and modalities subtitles rhetoric. This study uses Descriptive Research Methods, Social Semiotics research analysis method MAK Halliday, with the constructivist paradigm that sees social reality, as a result of construction, and the truth is a social reality is relative. Construction of meaning as verbal analysis are: speech style is dominated by Ethos style which indicates the case as a result of political engineering Susilo Bambang Yudhoyono (SBY); defense (pledoi or white book Anas); Anas personal imaging with style feel